Microbial abundance and diversity in water, and immune parameters of red tilapia reared in bioflocs system with different fish density (25 fish/m3, 50 fish/m3, and 100 fish/m3) - Frid Agustinus; . Widanarni; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRACT